Villages with land use plan for joint village land use planning in Kiteto, Kilindi, Mvomero and Chalinze landscape - Kalenzi, Deus (International Livestock Research Institute, 2018)
Map showing villages that had village land use plans in 2018, in Kiteto, Chalinze, Kilindi and Mvomero districts, Manyara, Tanga, Morogoro and Coastal (Pwani) regions, Tanzania.